Performance evaluation of an optimized PID controller for propofol and remifentanil coadministration in general anesthesia. (March 2021) - Schiavo, Michele; Padula, Fabrizio; Latronico, Nicola; Merigo, Luca; Paltenghi, Massimiliano; Visioli, Antonio
Abstract: In this paper we present the preliminary clinical results obtained with a PID control scheme for propofol and remifentanil coadministration during general anesthesia. The bispectral index scale is the only process variable, and the extra degree of freedom in the control architecture is handled by introducing an appropriate ratio between the infusion rates of the two drugs. The parameters of the PID controller are selected by means of an optimization procedure. The proposed control system automatically handles both the induction and the maintenance phase by using two different set of tuning parameters, specifically optimized for each phase, and a gain scheduling approach. The preliminary clinical evaluation of our controller has been obtained on ten patients undergoing general anesthesia during plastic surgery. The system has been able to satisfactorily induce and maintain anesthesia in the entire population of patients, without requiring any manual intervention by the anesthesiologist, thus confirming the effectiveness of the overall design approach.